Experiences Using Media Health Claims to Teach Evidence-Based Practice to Healthcare Students: A Mixed Methods Study [version 3; peer review: 2 approved, 2 approved with reservations] - Astrid Dahlgren; Marianne Molin; Jürgen Kasper; Lisa Garnweidner-Holme; Hilde Tinderholt Myrhaug; Ida-Kristin Orjasaeter Elvsaas (F1000Research)
Background A multifaceted and interactive teaching approach is recommended for achieving proficiency in evidence-based practice, with critical thinking considered vital for connecting theory and practice. In this context, we advocate the strategic use of health claims in media to promote critical thinking and provide an accessible entry point to evidence-based practice for early-stage university healthcare students. Method We conducted a convergent mixed methods study, including a cross-sectional survey with structured and open-ended questions as well as focus group interviews, at the Faculty of Health Sciences, Oslo Metropolitan University, during the 2020-2021 academic year. Participants were bachelor’s students in bioengineering, physiotherapy, social education, and occupational therapy. We employed a blended learning approach, combining digital learning resources, teaching in critical assessment of health claims and evidence-based practice, and a concurrent group exam assignment centered around health news. The outcome measures included students’ experiences integrating health claims into evidence-based practice teaching and their experiences with teaching approaches, including the group exam. Results Out of 446 participants, 136 (30.5%) responded to the structured questions in the survey. In response to the open-ended questions within the survey, 109 (80.1%) of the respondents shared positive experiences about the course, while 98 (72%) suggested improvements. Additionally, 25 students participated in focus group interviews. Synthesizing the results, we found that students viewed the inclusion of health claim assessment as a useful entry point for learning evidence-based practice. In addition, both the blended learning design and the group exam were identified as contributors to a positive perception of learning outcomes from the course. Conclusions Integrating critical reflection on media health claims into evidence-based practice education, alongside a blended learning approach and a group exam, may be beneficial for educating bachelor’s healthcare students. However, further rigorous study designs are needed to assess the effect of the course on learning outcomes. Registration DOI 10.5281/zenodo.6985449